Confrontation and reconcilement in contemporary Native American theater: Two Native American plays - López Pérez, Sidoní (HUMAN REVIEW. International Humanities Review / Revista Internacional De Humanidades, 2025)
Contemporary Native American theater consists of a long list of plays which normally include indigenous and mixed-blood characters who often find themselves living between two worlds, that is, Native culture and white American society. Therefore, it is common to find a significant confrontation and conflict between the two cultures, which is usually solved at the end of the plays with the characters’ reconcilement or synthesis between their Native heritage and the white domineering society. In this way, Native Americans can ensure their Native cultural existence and survival whilst simultaneously adapting to the changes and customs required by white American society.
Confrontación y reconciliación en el teatro nativo americano contemporáneo
El teatro nativo-americano contemporáneo contiene una larga lista de obras que normalmente incluyen personajes indígenas y mestizos que a menudo viven entre dos mundos, es decir, la cultura nativa y la sociedad blanca americana. Por ello, suelen surgir enfrentamientos y conflictos entre ambas culturas, que normalmente se resuelven al final de las obras con la reconciliación o síntesis de los personajes entre su herencia cultural nativa y la sociedad blanca dominante. Así, los indígenas pueden asegurar su existencia y supervivencia cultural nativa al mismo tiempo que se adaptan a los cambios y costumbres que requiere la sociedad blanca americana.
Keywords: Native American culture; White culture; theater; confrontation; tradition; modernity; reconcilement